(untitled) (Third Sector Social Economic Review, 2021)
The aim of this paper is to reveal the mediating role of corporate reputation on the relationship between corporate social responsibility and brand loyalty. The data is gathered by online questionnaire form applied on the samples determined by convenient sampling methodology. In the study, first, explanatory and two-stage confirmatory factor analysis was performed to test the reliability and validity of corporate social responsibility and corporate reputation scales in the relevant sample. Afterwards, mediation analysis was conducted with the help of structural equation modeling to determine the effect of the corporate reputation on the model. According to the findings, corporate social responsibility perceptions of bank customers affect their brand loyalty positively (β=0.276 p<0.01); but mediating effect of the corporate reputation perceptions of bank customers in this relationship changed the direction and size of the relationship (β=0.073 (p> 0.05). These results show that corporate reputation plays a full mediating role in the relationship between corporate social responsibility and brand loyalty. The research provides empirical results regarding the importance of corporate social responsibility for sustainable competition in the sector from the perspective of bank customers.